Psychological Effects of Social Isolation Due to Quarantine in Chile: An Exploratory Study - Dagnino, Paula; Anguita, Verónica; Escobar, Katherine; Cifuentes, Sofía (Frontiers in Psychiatry, 2020)
COVID-19 has impacted the entire world. Quarantine disrupts people’s lives, with high levels of stress and negative psychological impacts. Studies carried out mostly in the Far East, Europe or the United States have started to provide evidence on survivors, frontline health-care workers, and parents. The present study is the first survey to be carried out in Latin America (Chile). It aims to: (a) explore perceived psychological impact and future concerns; (b) vulnerability factors; (c) perceived psychological impacts on participants whose psychological help was interrupted and have actual online psychotherapy, and (d) future need for psychological help. Procedure: an online survey was carried out (first two weeks of lockdown in Santiago), including socio-demographic data, perceived psychological impact, future concerns, and psychological support. Participants: 3,919 subjects, mostly women (80%). Results: the main perceived psychological impacts; concern (67%) and anxiety (60%). Future concerns; general health (55.3%), employment (53.1%) and finances (49.8%). Youngers had a high perceived psychological impact (p’ s<.01) and concerns about employment, finances, mental health, stigma, and general health (p’s <.001). Women reported more perceived psychological impact than men (p’s < .05). Men reported mainly boredom (X2 = 11.82, gl = 1, p < .001). Dependent employees experienced more boredom, anxiety, distress, sleep problems, an inability to relax, and a lack of concentration than the self-employed (p’s < .05). While the latter reported future concerns about employment and finances (p’s <.001), dependent employees reported them on their general and mental health (p’s <.001). Regarding psychological support, 22% of participants were receiving it before lockdown. They showed more perceived psychological impact than those who were not (p’s <.01), and 7% of them had online psychotherapy, reporting excellent (32.1%) or odd but working (65.2%) results. Finally, of the total sample, almost half of the participants (43.8%) felt they would need emotional support after this pandemic, and these are the ones that also showed higher perceived psychological impact (p’s <.001). This study confirms the presence of perceived negative impacts and concerns about the future. Also, there are vulnerable groups, such as women, younger people, the self-employed, and people with psychological processes that were interrupted.